MARKERS OF RISK FACTORS FOR CARDIOVASCULAR DISEASE - N. H. Bashirov (Евразийский Кардиологический Журнал)
Objective: To study the role of risk factors for cardiovascular diseases to optimize their pathogenetic diagnosis.Material and research methods. At the initial stage of clinical trials, all participants (n = 200) were questioned with age-sex characteristics and the main risk factors for cardiovascular diseases (alcohol abuse, smoking, obesity, stress). Biochemical and clinical studies were carried out in two groups of patients, 15 people in each group (the first main group - in addition to bad habits, there is an obesity factor, the second control group - bad habits are detected, but in the absence of obesity) as part of preventive medical examinations.The results of research. When studying psychosocial risk factors for the development of diseases of the cardiovascular system, a higher prevalence rate was noted for men in depression indicators - 26.3% of cases, and in the group of female patients the results were almost 2.5 times lower and amounted to only 15.0%. in both groups of healthy individuals, a low level of the frequency of occurrence of overweight and obesity was observed, compared with the main group, which were diagnosed in 28.6% of cases in the male half of the subjects, and among the representatives of the opposite sex, the indicator was 24.0%. The proportion of obese women in the main and control groups was higher than men by almost 1.5 times. Against the background of obesity and the presence of signs of non-alcoholic fatty degeneration of the liver, in comparison with patients with normal body weight, certain violations were detected in the form of a higher level in the blood of the liver enzyme ALAT - 35.2 ± 1.57 U / L and 21.3 ± 0 95 U / L, respectively, in the first main group and in the second control group.Conclusions. Thus, it was found that the cause of cardiovascular diseases, in particular, cardiac automatism disorders, stroke, myocardial infarction due to metabolic and psychoemotional disorders are overweight and obesity, which worsen the prognosis of CVD, creating the prerequisites for the development of complications.